THE EFFECT OF IMPLEMENTING THE PROBLEM-BASED LEARNING (PBL) MODEL WITH THE KIPIN SCHOOL 4.0 APPLICATION MEDIA ON THE LEARNING OUTCOMES OF SEVENTH-GRADE STUDENTS AT STATE JUNIOR HIGH SCHOOL - Hidayah, Nur; Maasawet, Elsje Theodora; Palenewen, Evie; Tindangen, Makrina (Jurnal Pendidikan Matematika dan IPA, 2025)
The study examines the effects of implementing the Problem Based Learning instructional approach, along with the Kipin School 4.0 application, on the academic achievement of 7th grade students at SMP Negeri 8 Bontang. The purpose of this study is to find out to evaluate the effects of implementing the Problem Based Learning (PBL) instructional strategy, in conjunction with the Kipin School 4.0 Application Media, on the academic performance of seventh-grade students at SMP Negeri 8 Bontang. Ecology and biodiversity content for the academic year 2023/2024. The type of research used by the researcher is Quasi Experiment (pseudo experiment) with a quantitative approach. Purposive sampling technique with a sample of 66 students. The data analysis technique utilizes the independent sample t-test with a significance level of 5%. The data analysis results demonstrate a statistically significant value. The two-tailed p-value is 0.00, indicating that it is lower than the predetermined significance level of 0.05. In addition, the t-test statistic (3.674) exceeds the essential t-value (1.669). Thus, it can be inferred that implementing the Problem Based Learning (PBL) instructional approach using the Kipin School 4.0 program has a substantial influence on the academic achievements of 7th-grade students at SMP Negeri 8 Bontang.